Timor Leste - Expanding Near-Term Agricultural Exports - Main Report - World Bank (World Bank, 2012)
The Government of Timor-Leste (GOTL) is committed to the development of the non-oil economy by enabling the diversification of domestic production and trade integration. The objective of the Timor-Leste Diagnostic Trade Integration Study (DTIS) is to agree on priority actions to help overcome constraints to expanding agricultural exports in the near-term. It supports the government's efforts to develop a broader international trade strategy, which may include strategic sectors such as tourism and fisheries. The focus of the DTIS is on short-term results in areas with immediate export potential. It therefore looks only at the agriculture sector. Achieving export growth and diversification are essential for supporting overall economic growth and employment generation. Non-oil export growth is critical in light of the external sustainability risks of depending on exhaustible petroleum exports. Expanding output for domestic consumption is also a priority and may help reduce dependence on imports. Policy actions to expand exports will impact positively on domestic trade as well. Timor-Leste faces the challenge of having to mostly create a non-oil export sector, rather than reviving one that is stagnant or destroyed because of conflict. This context is quite unique even when compared to similar small-island or post-conflict countries.